Pengaruh Ekstrak Kulit Batang Angsana (Pterocarpus indicus Willd.) Terhadap Kualitas Sperma Epididimis Mencit (Mus musculus L. Swiss Webster) - Dona, Fitria; Sumarmin, Ramadhan; Indriati, Gustina (STKIP PGRI Sumbar, 2014)
Abstract:Â This study aims to determine the effect of bark extract (Pterocarpus indicus Willd.) on the quality of epididymal mice spermatozoa (Mus musculus L. Swiss Webster). This experiment used a Completely Randomized Design (CRD) consisting of 3 treatments and 9 replications. K is the control with no treament and bark extract. Treatment of P1 and P2 are given treament Â bark extract orally for 35 days at dosages of 0,1gr/b.w and 0,2 gr/ b.w, After treament the mice decapitatied and surgical the epididymal taken to count the number of sperm with Improved Neubauer method for calculating and used Eosin staining of normal and abnormal spermatozoa. Data were analyzed by ANOVA (Analysis Of Varians) and followed DNMRT. The result showed the average number of spermatozoa P2 is 56.38 Ã 105 significantly different (p < 0.05) compared to P1 54.05 Ã 105 and K48.22 Ã 105. While the average number of abnormal spermatozoa in K 12.27 Ã 105 and P1 23.33 Ã 105 and P227.94 Ã 105. It can be concluded that the bark extract given orally for 35 days can reduce the quality of sperm and increase abnormal of sperm.